2020
DOI: 10.3390/molecules25071607
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Photodynamic Activity against Bladder Cancer Cells of Novel Triazole-Porphyrin Derivatives

Abstract: Novel triazole-porphyrin derivatives (TZ-PORs) were synthesized through the Heck reaction and then incorporated into polyvinylpyrrolidone (PVP) micelles. After verifying that this incorporation did not compromise the photophysical and chemical features of TZ-PORs as photosensitizers, the phototoxicity of the formulations towards cancer cells was screened. Biological studies show high photodynamic activity of all PVP-TZ-POR formulations against a bladder cancer cell line with a particular highlight to PVP-TZ-PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…VPD was selected as the monomer to prepare PVP formulations due to their already reported features, namely, pharmacokinetic and pharmacological properties, non-toxicity, and water-solubility of the obtained micelles [ 96 ]. This strategy allows to improve the hydrophilicity of biologically active drugs and is being efficiently used to solubilize neutral porphyrin-base PS in water with positive effects in photodynamic processes [ 97 , 98 , 99 , 100 ]. Moreover, this carrier demonstrated to be non-toxic for both normal and cancer cells after PDT treatment [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VPD was selected as the monomer to prepare PVP formulations due to their already reported features, namely, pharmacokinetic and pharmacological properties, non-toxicity, and water-solubility of the obtained micelles [ 96 ]. This strategy allows to improve the hydrophilicity of biologically active drugs and is being efficiently used to solubilize neutral porphyrin-base PS in water with positive effects in photodynamic processes [ 97 , 98 , 99 , 100 ]. Moreover, this carrier demonstrated to be non-toxic for both normal and cancer cells after PDT treatment [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…This strategy allows to improve the hydrophilicity of biologically active drugs and is being efficiently used to solubilize neutral porphyrin-base PS in water with positive effects in photodynamic processes [ 97 , 98 , 99 , 100 ]. Moreover, this carrier demonstrated to be non-toxic for both normal and cancer cells after PDT treatment [ 100 ]. However, to the best of our knowledge, this approach has not been used with benzoporphyrin-type derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Next, 130 was submitted to a metallation reaction with Zn(OAc) 2, giving rise to 2‐bromo‐5,10,15,20‐tetraphenylporphyrinatozinc (II) 131 , which in turn undergoes a Heck coupling reaction with 4‐vinyl‐1,2,3‐triazoles 88 . Finally, the demetallation of 132 using trifluoroacetic acid (TFA) furnishes β‐substituted triazole‐porphyrins 133 in quantitative yields [93] . Importantly, singlet oxygen generation studies have revealed that all PVP‐ 133 formulations presented superior ability of producing ROS than PVP‐TPP, which is used as reference.…”
Section: Synthetic Strategies Toward 123‐triazole Derivativesmentioning
confidence: 99%
“…Importantly, singlet oxygen generation studies have revealed that all PVP‐ 133 formulations presented superior ability of producing ROS than PVP‐TPP, which is used as reference. In addition, the photodynamic effect of such formulations was evaluated in human bladder cancer cells (HT‐1376 cell line), and the results have shown that those are effective for PDT [93] …”
Section: Synthetic Strategies Toward 123‐triazole Derivativesmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a non-invasive approach to treat oncological and non-oncological diseases (Figueira et al, 2014;Kwiatkowski et al, 2018;Mesquita et al, 2018a,b;Gazzi et al, 2019;Negri et al, 2019;Castro et al, 2020;Gomes et al, 2020;Lee et al, 2020). PDT is a clinically approved treatment based on the activation of a photosensitizer (PS) by the light of a specific wavelength, in the presence of molecular oxygen to produce reactive oxygen species (ROS), resulting in neoplastic cell death (Agostinis et al, 2011;Bogoeva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%